Dislodgement of a right atrial thrombus and subsequent pulmonary thromboembolism following tracheal stent deployment in a dog. Issue 6 (13th April 2016) - Preston, Ayla R.; Sullivan, Lauren A.
Abstract: Objective: To report the management of a dog that required 2 treatments with mechanical ventilation; firstly for severe tracheal collapse and secondly following deployment of a nitinol tracheal stent that immediately preceded a nonoxygen responsive pulmonary thromboembolism (PTE), suspected to have originated from the right atrium. Case Summary: A 9‐year‐old female spayed Shetland Sheepdog was presented for management of a gallbladder mucocoele. Pertinent history included iatrogenic hyperadrenocorticism and tracheal collapse. The dog became clinical for tracheal collapse following laparoscopic cholecystectomy. Thoracic radiographs revealed moderate to severe tracheal collapse at the level of the thoracic inlet. Arterial blood gas was consistent with hypoventilation and mechanical ventilation was instituted. Given the severity of tracheal collapse, self‐expanding nitinol tracheal stent placement was elected. Immediately following tracheal stent placement, the dog developed nonoxygen responsive hypoxemia requiring mechanical ventilation. Additional diagnostic tests revealed changes consistent with a PTE and a large thrombus in the right atrium. The dog was humanely euthanized. New or Unique Information Provided: Dislodgement of a preexisting atrial thrombus has not been described as a complication following tracheal stent deployment. Additionally, although PTE is frequently considered to be oxygen responsive, it may not be if the embolism is severe enough.